Local Treatment of Desmoid Tumors: An Update - Quek, Lawrence Han Hwee; Chan, Lester Wai Mon; Pua, Uei (Seminars in Interventional Radiology, 2024)
Desmoid tumors (DTs) are rare fibroblastic proliferations, characterized by infiltrative growth and a propensity for local recurrence. Traditional strategies such as surgery, radiotherapy, and chemotherapy are the mainstays of treatment, each with its limitations and associated risks. The trend in DT management leans toward a “wait-and-see” strategy, emphasizing active surveillance supported by continuous MRI monitoring. This approach acknowledges the unpredictable nature of the disease, and a multidisciplinary management of DT requires a nuanced approach, integrating traditional therapies with emerging interventional techniques. This review highlights the emerging role of minimally invasive interventional radiological technologies and discusses interventional radiology techniques, including chemical, radiofrequency, microwave, cryoablation, and high-intensity focused ultrasound ablations as well as transarterial embolization.
Keywords: desmoid tumor; radiofrequency ablation; microwave ablation; transarterial chemoembolization; interventional radiology